Pengembangan Media Articulate Storyline Berbasis Pendekatan Culturally Responsive Teaching untuk Meningkatkan Hasil Belajar Siswa Kelas III Sekolah Dasar - Rara Salsabila Azzahra; Erwin Putera Permana; Efa Wahyu Prastyaningtyas (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
The purpose of this study was to describe the validity, practicality, and effectiveness of the Articulate Storyline learning media based on the Culturally Responsive Teaching (CRT) approach on the material of East Java Cultural Diversity for third-grade students of SDN Burengan 3, Kediri City. This study used the Research and Development (R&D) method with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 28 third-grade students of SDN Burengan 3, Kediri City. Data collection techniques included observation, interviews, questionnaires, and tests. Data were analyzed using percentage analysis to measure validity and practicality, as well as the N-Gain test to measure the effectiveness of the media. The results showed that the media obtained a percentage of material expert validation of 90% and media expert validation of 90% with a very valid category. The results of the practicality test obtained a percentage of teacher responses of 90% and student responses of 93.6% with an average of 91.8% which is included in the very practical category. The effectiveness test results showed an N-Gain value of 0.795 in the limited trial and 0.78 in the extensive trial, with a high score. Thus, the Articulate Storyline learning media based on the CRT approach was declared valid, practical, and effective in improving student learning outcomes in the subject of East Javanese Cultural Diversity. This research contributes to the development of technology-based learning media integrated with local culture to create more interactive, contextual, and meaningful learning.